csc [cos^-1(-square root of 3 divided by 2)]

= csc(5pi/6)

= 1/sin(5pi/6)

= 2

Tutors, please sign in to answer this question.

Scottsdale, AZ

csc [cos^-1(-square root of 3 divided by 2)]

= csc(5pi/6)

= 1/sin(5pi/6)

= 2

Evan F.

Mathematics graduate looking to enhance your mathematics ability.

Cambria Heights, NY

4.9
(315 ratings)

John P.

Tutor of math and physics, recent college graduate

Short Hills, NJ

5.0
(20 ratings)

- Precalculus 1527
- Math Help 5358
- Math 9681
- Math Help For College 1384
- Pre Calculus 377
- Math Equations 956
- Pre-Calculus 341
- Math Problem 1005
- Mathematics 566
- Math Question 789